FÂ’ILIYAH BARNÂMAJ QÂIM ‘ALA AL-TA’ALLUM AL-TA’ÂWUNÎ FÎ TANMIYAH MAHÂRÂT AL-TAFKÎR AL-NÂQID - Abdillah, Ridho; Dahab, Abou (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2020)
The aim of the research is to know the effectiveness of a program based on cooperative learning in developing critical thinking skills among learners of the Arabic language speaking other languages. The research method used in this research is the semi-experimental approach based on the design of one group with two pre and post-tests. The sample consisted of (46) fourth-level educated learners at the Institute of Arabic Language Teaching at the Islamic University in Madinah. The research tools were defined in the list of necessary critical thinking skills, and tests of critical thinking skills. Statistical methods: The Pearson correlation coefficient, Alpha Cronbach coefficient, T-test, ETA square, and Black equation. The research resulted in a statistically significant difference at (0.01) between the mean scores of the research sample in the pre and post measurements in the test of critical thinking skills as a whole and separately in favor of telemetry.